Effect of special exercises using a device designed to develop the most important motor abilities and offensive skills for handball players at ages (12-14) years old - Jassim, M. A.; Ali, M. H. (Annals of the Romanian Society for Cell Biology, 2021)
The importance of this study is evidenced by the preparation of special exercises usinga device designed for ages (12-14) years, as the researcher believes that these will have a positive effect on some of the players' better motor abilities, which is reflected in the performance of the basic offensive skills of handball being one of the critical skills the match is poignant to win and through the researchers' observation that the exercises used by some coaches for the age groups lack the use of modern educational methods and tools in handball, which may no longer be sufficient to effect theacquisition of motor abilities based on the main work of basic handball skills, as the exercises were limited to the use of traditional methods or tools prevalent in education, which does not allow diversification and change to occur, and given that working with age groups requires a period of time for the correct construction process for the stages of learning, hence the idea of research by designing a device that develops motor abilities offensive skills,the research aimed to identify the preparation of special exercises using a device designed for handball players aged 12-14 years, in addition to identifying the effect of exercises using the device designed to develop the most important movement capabilities and offensive handball skills, and the researchers assume that the exercises for using the device designed by the researchers asignificant effect in developing the most important motor abilities and offensive handball skills.As for the research methodology: The researchers used the experimental method to solve the research problem, while the research sample was chosen by a simple random method, whose number is (20) players. After excluding goalkeepers for the specificity of their exercises, in addition to excluding the players of the reconnaissance experiment, the research sample reached (12) players, and they were divided into two groups (experimental, control) equally and by (6) players in each group,as the experimental group used special exercises using the designer's device,as for the control group, they train under the supervision of the trainer and the curriculum for specialized schools for handball, and after the main experiment was applied to them, the results were analyzed and processed using (spss), and the researchers reached theresults, including that the exercises using the designed device positively affected the development of the most important motor abilities and offensive skillsfor handball players.The researchers recommended that this type of exercise should be applied to different age groups and samples in order to develop the motor performance and skills of handball.